Silicon-carbon composite material, preparation method thereof and lithium ion battery

By improving the binding force between nanosilicon and porous carbon in silicon-carbon composite materials, and coating fast ion conductors and resins, the problems of poor interface stability and electrochemical performance attenuation of silicon-carbon composite materials during charging and discharge are solved, and its fast charging performance is significantly improved.

CN119591156APending Publication Date: 2025-03-11BEIJING SOLIDE NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411772876.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing silicon-carbon composite materials have problems such as poor interface stability and fast electrochemical performance decay during charging and discharging, resulting in poor fast charging performance.

Method used

By treating porous carbon in a fluidized bed, amino porous carbon is generated and nanosilicon is deposited with hydroxysilane at high temperatures, thereby increasing the binding force of nanosilicon with porous carbon. At the same time, the fast ion conductor and resin are coated through ultraviolet photopolymerization and oxidation and liquid phase method to improve the conductivity and structural stability of the material.

Benefits of technology

It significantly improves the conductivity, ionic conductivity and structural stability of silicon-carbon composite materials, improves its fast charging performance, and is suitable for negative electrode materials for high-energy density lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591156A_ABST
    Figure CN119591156A_ABST
Patent Text Reader

Abstract

The invention relates to a silicon-carbon composite material, a preparation method thereof and a lithium ion battery. The preparation method comprises the following steps: adding porous carbon into a fluidized bed, heating and introducing alkaline mixed gas to obtain amino porous carbon; transferring the amino porous carbon into fluidized bed equipment, vacuumizing, heating, and introducing hydroxyl silane gas for nano silicon deposition; after deposition, introducing ultraviolet light for polymerization and oxidation to obtain a modified silicon-carbon precursor material; transferring the modified silicon-carbon precursor material into a tubular furnace, introducing inert gas to discharge air in the tube, and performing first carbonization to obtain a silicon-carbon material; and adding the resin into an organic solvent, adding the fast ion conductor and the silicon carbon material to be uniformly dispersed, performing spray drying, and performing secondary carbonization to obtain the fast ion conductor coated silicon carbon composite material. The preparation method provided by the invention is simple and efficient, and the prepared silicon-carbon composite material can improve the fast charging performance and is suitable for a negative electrode material of a high-energy-density lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a silicon-carbon composite material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] In modern society, with the rapid development of portable electronic devices, electric vehicles and renewable energy systems, the demand for high energy density and high power density lithium-ion batteries is increasing. Lithium-ion batteries have become the main energy storage devices due to their advantages such as high energy density, long cycle life and low self-discharge rate. However, currently commercial lithium-ion batteries mainly use graphite as the negative electrode material, and its theoretical specific capacity is only 372 mAh / g, which is difficult to meet the demand for high energy density batteries in the future.

[0003] Silicon (Si) is considered one of the most promising negative electrode materials for lithium-ion batteries due to its extremely high theoretical specific capacity (about 4200 mAh / g). However, silicon undergoes a huge volume expansion (about 300%) during the charge and discharge process, resulting in the destruction of the electrode structure and a sharp decrease in cycle life. In addition, silicon has poor conductivity, which also affects its electrochemical performance.

[0004] Carbon materials, such as porous carbon, are widely used in the preparation of silicon-carbon composites due to their excellent conductivity, chemical stability and structural controllability. Porous carbon can not only effectively buffer the volume expansion of silicon, but also provide a rich pore structure, which is conducive to the penetration of electrolyte and the transmission of lithium ions. However, pure silicon-carbon composites still have some problems in the long cycle process, such as poor interface stability and rapid electrochemical performance decay.

[0005] In order to further improve the electrochemical performance of silicon-carbon composite materials, the existing technology dopes, modifies and coats silicon-carbon materials to improve the electronic or ionic conductivity of the material and improve the rate performance. However, in the existing silicon-carbon composite materials, the poor electronic conductivity of the porous carbon itself and the large interface impedance between the porous carbon and nano-silicon result in a large resistance to the insertion and extraction of lithium ions during the charging and discharging process. At the same time, the amorphous carbon coating layer of the outer shell has many defects and a non-dense structure due to the low carbonization temperature, resulting in a relatively large impedance of the material. The superposition of the two causes the deviation of the fast charging performance of the existing silicon-carbon composite materials.

[0006] Therefore, it is necessary to improve the existing technology. Summary of the invention

[0007] In the prior art, the existing silicon-carbon composite material has poor fast charging performance due to the superposition effect of the inner core and the outer shell. Therefore, the present invention provides a silicon-carbon composite material and a preparation method thereof, and a lithium-ion battery for solving the above problems.

[0008] To achieve the above object, in a first aspect, the present invention provides a method for preparing a silicon-carbon composite material, which comprises the following steps: S1, adding porous carbon to a fluidized bed, heating to 800-1100°C, and introducing alkaline mixed gas to obtain amino porous carbon; S2, transferring the amino porous carbon to a fluidized bed device, evacuating to ≤0.1Mpa, heating to 500-700°C, introducing hydroxy silane gas to deposit nano-silicon; after deposition, introducing ultraviolet light polymerization oxidation to obtain a modified silicon-carbon precursor material; S3, transferring the modified silicon-carbon precursor material to a tube furnace, introducing an inert gas to exhaust the air in the tube, and obtaining a silicon-carbon material after the first carbonization; S4. According to the mass ratio of silicon-carbon material: fast ion conductor: resin = 100: (1-5): (5-15), the resin is added to an organic solvent to prepare a solution with a mass concentration of 1-10wt%, the fast ion conductor and the silicon-carbon material are added and dispersed evenly, and a second carbonization is performed after spray drying to obtain a silicon-carbon composite material coated with a fast ion conductor.

[0009] In one implementation, in S1, the volume ratio of the alkaline gas to the argon gas in the alkaline mixed gas is (1-5):10, and the alkaline gas is any one of NH3, PH3 and N2H4.

[0010] In one implementation, in S1, the alkaline mixed gas is introduced at a flow rate of 100-500 SCCM and for a time of 60-600 min.

[0011] In one implementation, in S2, the hydroxysilane gas is any one of triphenylhydroxysilane, diphenyldihydroxysilane and dihydroxydiphenylsilane.

[0012] In one implementation, in S2, the hydroxysilane gas is introduced at a flow rate of 100-300 SCCM, and the introduction time is 30-300 min.

[0013] In one implementation, in S2, the wavelength of the ultraviolet polymerization is 200-400 nm, and the irradiation intensity is 5000-15000 yw / cm 2 , the illumination time is 5~20min.

[0014] In one implementation, in S3 and S4, the temperature of the first carbonization and the second carbonization is 900-1200° C., and the carbonization time is 1-6 hours.

[0015] In one implementation, in S4, the fast ion conductor is any one of lithium zirconium phosphate, lithium vanadium phosphate, lithium cerium phosphate and lithium niobate; the resin is any one of phenolic resin, epoxy resin, furfural resin and urea-formaldehyde resin; the organic solvent is any one of ethyl acetate, chloroform, toluene and acetone.

[0016] In a second aspect, the present invention further provides a silicon-carbon composite material, which is prepared by any one of the above-mentioned methods for preparing the silicon-carbon composite material.

[0017] In a third aspect, the present invention further provides a lithium-ion battery, which comprises the above-mentioned silicon-carbon composite material as a negative electrode material.

[0018] Beneficial effects: In the present invention, amino porous carbon and hydroxy silane are reacted and cracked at high temperature, so as to enhance the binding force between nano-silicon and porous carbon and reduce the interface impedance; at the same time, amino porous carbon is nitrogen-doped porous carbon in the subsequent high-temperature carbonization process, which can enhance the electronic conductivity of the material; By oxidatively polymerizing the silicon-carbon precursor, the defects of the material are reduced, and a protective film is formed on the surface of the material after oxidative polymerization, which reduces its side reactions and improves its processing and manufacturing properties; By using a liquid phase method, a fast ion conductor is mixed with a resin solution, carbonized, and a fast ion conductor amorphous carbon material is obtained, which is then coated on the surface of a silicon-carbon material to improve the ionic and electronic conductivity of the material. The coating layer has good compatibility with the electrolyte, which can improve storage and cycle performance. By depositing nano-silicon in porous carbon and introducing fast ion conductors and resins for coating, the electrical conductivity, ionic conductivity and structural stability of the silicon-carbon composite material are significantly improved, and its fast charging performance is improved; the preparation method provided by the present invention is simple and efficient, and the prepared silicon-carbon composite material has excellent electrochemical properties and is particularly suitable for negative electrode materials of high energy density lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a flow chart of the steps of the method for preparing the silicon-carbon composite material provided by the present invention; Figure 2 is a SEM image of the silicon-carbon composite material provided in Example 1.

[0020] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0022] See also Figure 1 , Figure 1 The present invention provides a method for preparing a silicon-carbon composite material, which comprises the following steps: S1, adding porous carbon to a fluidized bed, heating to 800-1100°C, and introducing alkaline mixed gas to obtain amino porous carbon; S2, transferring the amino porous carbon to a fluidized bed device, evacuating to ≤0.1Mpa, heating to 500-700°C, introducing hydroxy silane gas to deposit nano-silicon; after deposition, introducing ultraviolet light polymerization oxidation to obtain a modified silicon-carbon precursor material; S3, transferring the modified silicon-carbon precursor material to a tube furnace, introducing an inert gas to exhaust the air in the tube, and obtaining a silicon-carbon material after the first carbonization; S4. According to the mass ratio of silicon-carbon material: fast ion conductor: resin = 100: (1-5): (5-15), the resin is added to an organic solvent to prepare a solution with a mass concentration of 1-10wt%, the fast ion conductor and the silicon-carbon material are added and dispersed evenly, and a second carbonization is performed after spray drying to obtain a silicon-carbon composite material coated with a fast ion conductor.

[0023] Specifically, in S1, the volume ratio of alkaline gas to argon in the alkaline mixed gas is (1-5):10, and the alkaline gas is any one of NH3, PH3 and N2H4. The alkaline mixed gas is introduced at a flow rate of 100-500 SCCM, and the introduction time is 60-600 min. By treating porous carbon with the alkaline mixed gas, amino porous carbon can be generated, thereby improving the reactivity and surface area of ​​the material. In this step, the raw material provides porous carbon as a carbon material, and its porous structure and conductivity improve the electronic conductivity and structural stability of the material, solving the problem of volume expansion of silicon during charging and discharging.

[0024] In S2, the hydroxysilane gas is any one of triphenylhydroxysilane, diphenyldihydroxysilane and dihydroxydiphenylsilane. The hydroxysilane gas is introduced at a flow rate of 100-300 SCCM and an introduction time of 30-300 min. By controlling the flow rate and introduction time of the alkaline mixed gas and the hydroxysilane gas, the chemical reaction is ensured to be fully and uniformly carried out. In addition, the wavelength of the ultraviolet polymerization is 200-400 nm, the irradiation intensity is 5000-15000 yw / cm2, and the illumination time is 5-20 min.

[0025] In the present invention, the nano-silicon is deposited to make the composite material finally obtained have a higher specific capacity, which can significantly improve the energy density of the battery. The nano-silicon is deposited by hydroxyl silane gas and then subjected to ultraviolet light polymerization oxidation, which can improve the surface modification effect of the silicon-carbon composite material and enhance the conductivity and stability of the material.

[0026] In S3 and S4, the temperature of the first carbonization and the second carbonization is 900~1200℃, and the carbonization time is 1~6h. Furthermore, in S4, the fast ion conductor is any one of lithium zirconium phosphate, lithium vanadium phosphate, lithium cerium phosphate and lithium niobate; the resin is any one of phenolic resin, epoxy resin, furfural resin and urea-formaldehyde resin; the organic solvent is any one of ethyl acetate, chloroform, toluene and acetone. Among them, the fast ion conductor can improve the ionic conductivity of the material and accelerate the charge and discharge reaction of the battery; the use of phenolic resin, epoxy resin, etc. as a binder can improve the mechanical strength and stability; the organic solvent helps to disperse and evenly mix the materials.

[0027] The present invention provides a plurality of embodiments and comparative examples and verification experiments to illustrate the technical solution of the present invention in detail.

[0028] Example 1 This embodiment provides a method for preparing a silicon-carbon composite material, comprising the following steps: S1. Add porous carbon to a fluidized bed, heat to 950°C, and introduce alkaline mixed gas (volume ratio, ammonia gas: argon gas = 3:10) at a flow rate of 300 SCCM for 300 min to obtain amino porous carbon; S2, transferring the amino porous carbon to a fluidized bed device, evacuating to 0.05 MPa, heating to 600°C, and introducing triphenylhydroxysilane gas at a flow rate of 200 SCCM for 150 min to deposit nano-silicon, and then introducing ultraviolet light (wavelength 300 nm, irradiation intensity 10000 yw / cm2) for polymerization and oxidation for 10 min to obtain a modified silicon-carbon precursor material; S3, transferring the modified silicon-carbon precursor material to a tube furnace, introducing argon inert gas to exhaust the air in the tube, and heating to 1100° C. for carbonization for 3 h to obtain a silicon-carbon material; S4. Add 10g of phenolic resin to 200g of ethyl acetate to prepare a solution with a mass concentration of 5wt%, then add 3g of lithium zirconium phosphate and disperse it evenly, then add 100g of silicon-carbon material and disperse it evenly, spray dry (inlet temperature 220°C, outlet temperature 100°C, flow rate 0.5kg / h, 4h), and carbonize the obtained material at a temperature of 1100°C for 3h to obtain a fast ion conductor coated silicon-carbon composite material.

[0029] Example 2 This embodiment provides a method for preparing a silicon-carbon composite material, comprising the following steps: S1, adding porous carbon to a fluidized bed, heating to 800°C, and introducing a phosphine mixed gas (volume ratio, phosphine:argon = 1:10) at a flow rate of 500 SCCM for 60 minutes to obtain amino porous carbon; S2, the amino porous carbon was transferred to a fluidized bed device, evacuated to 0.1 MPa, heated to 500°C, and diphenyldihydroxysilane gas was introduced at a flow rate of 100 SCCM for 300 min to deposit nano-silicon, and then ultraviolet light (wavelength 200 nm, irradiation intensity 5000 yw / cm 2 ) polymerization oxidation for 20 min to obtain a modified silicon-carbon precursor material; S3, transferring the modified silicon-carbon precursor material to a tube furnace, first introducing argon inert gas to exhaust the air in the tube, and heating to 900°C for carbonization for 6 hours to obtain a silicon-carbon material; S4. Add 10g of epoxy resin to 1000g of chloroform organic solvent to prepare a solution with a mass concentration of 1wt%, then add 1g of lithium vanadium phosphate and disperse it evenly, then add 100g of silicon-carbon material and disperse it evenly, spray dry (inlet temperature 220°C, outlet temperature 100°C, flow rate 0.5kg / h, 4h), and then carbonize the obtained material at a temperature of 900°C for 6h to obtain a fast ion conductor coated silicon-carbon composite material.

[0030] Example 3 This embodiment provides a method for preparing a silicon-carbon composite material, comprising the following steps: S1. Add porous carbon to a fluidized bed, heat to 1100°C, and introduce alkaline mixed gas (volume ratio, N2H4:argon = 5:10) at a flow rate of 100 SCCM for 600 min to obtain amino porous carbon; S2, the amino porous carbon was transferred to a fluidized bed device, evacuated to 0.05 MPa, heated to 700 ° C, and triphenylhydroxysilane gas was introduced at a flow rate of 200 SCCM for 150 min to deposit nano-silicon, and then ultraviolet light (wavelength 100 nm, irradiation intensity 10000 yw / cm 2 ) polymerization oxidation for 10 min to obtain a modified silicon-carbon precursor material; S3, transferring the modified silicon-carbon precursor material to a tube furnace, introducing argon inert gas to exhaust the air in the tube, and heating to 1200° C. for carbonization for 2 h to obtain a silicon-carbon material; S4. Add 10g of furfural resin to 100g of toluene to prepare a solution with a mass concentration of 10wt%, then add 2g of lithium cerium phosphate and disperse it evenly, then add 100g of silicon-carbon material and disperse it evenly, spray dry (inlet temperature 220°C, outlet temperature 100°C, flow rate 0.5kg / h, 4h), and carbonize the obtained material at a temperature of 1200°C for 2h to obtain a fast ion conductor coated silicon-carbon composite material.

[0031] Comparative Example 1: The difference from Example 1 is that ammonia is not introduced into S1, that is, porous carbon is used to replace amino porous carbon, and the rest is the same as Example 1.

[0032] Comparative Example 2: The difference from Example 1 is that no ultraviolet light is used for oxidative polymerization. The other steps are the same as Example 1.

[0033] Comparative Example 3: The difference from Example 1 is that lithium zirconium phosphate is not added to S3, and the rest is the same as Example 1.

[0034] The present invention conducts verification experiments on the above embodiments and comparative examples: (1) SEM test Figure 2 This is a SEM image of the silicon-carbon composite material in Example 1. As can be seen from the image, the material presents a spherical structure, the particle size is about 10 μm, and the size distribution is reasonable.

[0035] (2) Physical and chemical properties test: The specific surface area of ​​each silicon-carbon composite material was tested with reference to the national standard GB / T 38823-2020 "Silicon Carbon"; and the powder resistivity of each composite material was tested using a four-probe tester; the test results are shown in Table 1 below.

[0036] (3) Button battery test: The silicon-carbon composite materials corresponding to Examples 1 to 3 and Comparative Examples 1 to 3 were used as negative electrode materials for lithium-ion batteries to prepare button batteries according to the following method: A binder, a conductive agent and a solvent are added to each corresponding silicon-carbon composite material, stirred to make a slurry, coated on a copper foil, and dried and rolled to obtain a negative electrode sheet; the binder used is LA132, the conductive agent is SP (conductive carbon black), and the solvent is NMP. The usage ratio of the composite material, SP, LA132, and NMP is 95g:1g:4g:220mL; the electrolyte is a solution with LiPF6 as the electrolyte, and the concentration is 1mol / L, wherein the solvent is a mixture of EC and DEC in a volume ratio of 1:1; the metal lithium sheet is the counter electrode, and the diaphragm is a polypropylene (PP) film.

[0037] Each button cell was assembled in an argon-filled glove box, and then the electrochemical performance was tested. Specifically, the electrochemical performance was tested on a Wuhan Blue Electric CT2001A battery tester with a charge and discharge voltage range of 0.005V to 2.0V and a charge and discharge rate of 0.1C. At the same time, the room temperature charging DCR (0.1C, 50% SOC) and the cycle performance (0.1C / 0.1C, 100 weeks) of the front button cell were tested. At the same time, the gas production (45°C, 48h) of the negative electrode sheet and its full-charge expansion were tested. The test results are shown in Table 1 below.

[0038] Table 1, Physical and chemical properties test results of various embodiments and comparative examples: .

[0039] It can be seen from the data in Table 1 above that the specific capacity and the first efficiency of the silicon-carbon composite materials prepared in Examples 1 to 3 of the present application are significantly better than those in Comparative Examples 1 to 3; it can be seen from the experimental results that in the embodiments, the electronic conductivity of the material is improved by nitrogen-doping the silicon-carbon material, polarization is reduced, and the specific capacity of the material is improved. At the same time, through ultraviolet oxidation polymerization, the structural stability of the shell and its coated lithium salt compound are improved, gas production is reduced, irreversible capacity is reduced, and the first efficiency is improved. In addition, parameters such as DCR (direct current internal resistance), specific surface area, powder resistivity, gas production and full-charge expansion are significantly correlated with the fast charging performance of lithium-ion batteries. Examples 1 to 3 have lower internal resistance and resistivity, higher specific surface area, less gas production and smaller full-charge expansion relative to Comparative Examples 1 to 3. These parameters are all helpful to improve the fast charging performance of the battery.

[0040] (4) Soft pack performance test: The silicon-carbon composite materials corresponding to Examples 1 to 3 and Comparative Examples 1 to 3 were doped with 90% artificial graphite as negative electrode materials (i.e., negative electrode plates) and positive electrode ternary materials (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2), electrolyte and separator are assembled into a 5Ah soft-pack battery; wherein the separator is celegard 2400, the electrolyte is LiPF6 solution (the solvent is a mixed solution of EC and DEC with a volume ratio of 1:1, and the concentration of LiPF6 is 1.1 mol / L) to prepare the soft-pack battery.

[0041] The following performance tests are performed on each soft pack battery: The test conditions for the cycle performance test are: charge and discharge voltage range of 2.5~4.2V, temperature of 25±3.0℃, charge and discharge rate of 1.0C / 1.0C, and cycle number of 500 times; at the same time, the initial DCR of the battery is tested.

[0042] The test conditions of the rate test are: testing the constant current ratio of each soft-pack battery under 2C conditions = 2C constant current capacity / (2C constant current capacity + 0.1C constant voltage capacity); the test results are shown in Table 2 below.

[0043] Table 2, performance test results of soft-pack batteries provided in various embodiments and comparative examples: .

[0044] It can be seen from Table 2 that the rate and cycle performance of the soft-pack lithium-ion battery prepared by using the new silicon-carbon composite material provided by Examples 1 to 3 are significantly better than those of Comparative Examples 1 to 3. From the experimental results, it can be seen that the example material has low powder conductivity and its DCR, which can improve the constant current ratio of the material; from the results of Example 1 and Comparative Examples 1 to 3, it can be seen that during the preparation process, the operation of amino porous carbon, ultraviolet oxidation and fast ion conductor can have a positive effect on the capacity retention rate, initial DCR and 2C constant current ratio of the soft-pack battery, which helps to improve the initial efficiency of the battery.

[0045] In summary, the present invention reacts amino porous carbon with hydroxy silane at high temperature to crack it, thereby enhancing the binding force between nano-silicon and porous carbon and reducing the interface impedance; at the same time, the amino porous carbon is nitrogen-doped in the subsequent high-temperature carbonization process, which can improve the electronic conductivity of the material; By oxidatively polymerizing the silicon-carbon precursor, the defects of the material are reduced, and a protective film is formed on the surface of the material after oxidative polymerization, which reduces its side reactions and improves its processing and manufacturing properties; By using a liquid phase method, a fast ion conductor is mixed with a resin solution, carbonized, and a fast ion conductor amorphous carbon material is obtained, which is then coated on the surface of a silicon-carbon material to improve the ionic and electronic conductivity of the material. The coating layer has good compatibility with the electrolyte, which can improve storage and cycle performance. By depositing nano-silicon in porous carbon and introducing fast ion conductors and resins for coating, the electrical conductivity, ionic conductivity and structural stability of the silicon-carbon composite material are significantly improved, and its fast charging performance is improved; the preparation method provided by the present invention is simple and efficient, and the prepared silicon-carbon composite material has excellent electrochemical properties and is particularly suitable for negative electrode materials of high energy density lithium-ion batteries.

[0046] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a silicon-carbon composite material, characterized in that: The following steps are involved: S1, adding porous carbon to a fluidized bed, heating to 800-1100°C, and introducing alkaline mixed gas to obtain amino porous carbon; S2, transferring the amino porous carbon to a fluidized bed device, evacuating to ≤0.1Mpa, heating to 500-700°C, and introducing hydroxysilane gas to deposit nano-silicon; After deposition, ultraviolet light is introduced for polymerization and oxidation to obtain a modified silicon-carbon precursor material; S3, transferring the modified silicon-carbon precursor material to a tube furnace, introducing an inert gas to exhaust the air in the tube, and obtaining a silicon-carbon material after the first carbonization; S4. According to the mass ratio of silicon-carbon material: fast ion conductor: resin = 100: (1-5): (5-15), the resin is added to an organic solvent to prepare a solution with a mass concentration of 1-10wt%, the fast ion conductor and the silicon-carbon material are added and dispersed evenly, and a second carbonization is performed after spray drying to obtain a silicon-carbon composite material coated with a fast ion conductor.

2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: In S1, the volume ratio of the alkaline gas to the argon gas in the alkaline mixed gas is (1-5):10, and the alkaline gas is any one of NH3, PH3 and N2H4.

3. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: In S1, the alkaline mixed gas is introduced at a flow rate of 100-500 SCCM and for a time of 60-600 min.

4. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: In S1, in S2, the hydroxysilane gas is any one of triphenylhydroxysilane, diphenyldihydroxysilane and dihydroxydiphenylsilane.

5. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: In S1 and S2, the hydroxysilane gas is introduced at a flow rate of 100-300 SCCM and for a time of 30-300 min.

6. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: In S1, in S2, the wavelength of the ultraviolet polymerization is 200-400nm, and the irradiation intensity is 5000-15000yw / cm 2 , the illumination time is 5~20min.

7. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: In S1, in S3 and S4, the temperature of the first carbonization and the second carbonization is 900-1200°C, and the carbonization time is 1-6h.

8. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: In S1 and S4, the fast ion conductor is any one of lithium zirconium phosphate, lithium vanadium phosphate, lithium cerium phosphate and lithium niobate; the resin is any one of phenolic resin, epoxy resin, furfural resin and urea-formaldehyde resin; and the organic solvent is any one of ethyl acetate, chloroform, toluene and acetone.

9. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material is prepared by the preparation method according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: The silicon-carbon composite material according to claim 9 is used as a negative electrode material.

Citation Information

Cited By

  • Silicon-carbon negative electrode material, preparation method and application thereof, and battery negative electrode

    CN120933333A

  • Preparation method of fast ion conductor coated porous silicon carbon material

    CN121044567A

  • A method for preparing a porous silicon-carbon material coated with a fast ion conductor

    CN121044567B

  • Preparation method and application of fast ion conductor coated silicon-carbon composite material

    CN121812564A